VARIABEL EKONOMI MONETER YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DAN FINANCIAL INCLUSION BANK SYARIAH DI INDONESIA PERIODE 2010-2017 - Kholifatun Nahdliyah; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of exchange rate and money supply on economic growth and financial inclusion in Bank Syariah Period 2010-2017. The sample used is saturated samples, ie all parts of Sharia Bank, including Sharia Commercial Bank and Sharia Business Unit which in the last year of 2017 amounted to 13 Sharia Commercial Banks and 21 Sharia Business Units, furthermore this research uses time series data analysis by analyzing data from year to year. The research approach used is quantitative approach using analysis technique PLS (Partial Least Square) with four latent variables namely exchange rate and money supply as exogenous variable, economic growth as endogen intervention variable, and financial inclusion as endogen variable. The results of this study indicate: the exchange rate has a significant negative effect on economic growth, the money supply has a significant positive effect on economic growth, economic growth has a significant positive effect on financial inclusion of Sharia Bank.Keywords: exchange rate, money supply, economic growth, and financial inclusionREFFERENCESAyunia, Pridayanti.2012. Pengaruh Ekspor, Impor, Dan Nilai Tukar Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2002-2012. Surabaya : Universitas Negeri Surabaya.Demirguc-Kunt Dan Leora Klapper. 2013 Measuring Financial Inclusion. Jel Codes: G2, G21, O16, World Bank.Departemen Agama RI. 2004. Al-Quran dan Terjemahnya. Bandung: CV Penerbit J-Art.Ergin Akalpler, Dilgash Duhok. 2017. Does Monetary Policy Affect Economic Growth: Evidence From Malaysia. Journal Of Economic And Administrative Sciences.Vol. 34 Issue: 1, Pp.2-20, Emerald Insight. Ghozali, Imam. 2014. Partial Least Squares: Konsep dan Aplikasi Path Modeling Menggunakan Program XLSTAT-PLS. Semarang: Badan Penerbit Universitas Diponegoro.Gulo, Angandrowa. 2008. Analisis Pengaruh Aspek Fiskal Dan Moneter Terhadap Pertumbuhan ekonomi Indonesia. Visi (2008) 16 (3) 595 – 611, Issn 0853 - 0203Karim, Adiwarman.2004. Bank Islam Analisis Fiqh Dan Keuangan. Jakarta: Raja Grafindo Persada.Santoso, Teguh,Dkk., 2009. Dampak  Kebijakan Fiskal Dan Moneter Dalam Perekonomian Indonesia: Aplikasi Model Mundell-Fleming. Jurnal Organisasi Dan Manajemen, Volume 5, Nomor 2, September 2009, 108-128.Shihab, M. Quraish. 2009. Tafsir Al-Mishab:Pesan, Kesan, dan Keserasian Al-Quran. Jakarta: Lentera Hati.Sudarsono, heri.2003. Bank dan lembaga keuangan syariah Deskripsi dan ilustrasi. Yogyakarta : Ekonisia.Tambunan, Sely Nory. 2015.  Pengaruh Jumlah Uang Beredar Dan Pengeluaran Pemerintah Terhadap Produk Domestik Bruto  (Pdb) Indonesia. Jom Fekon Volume 2 No. 1 Februari 2015Todaro, Michael P. 2006. Pembangunan Ekonomi di Dunia Ketiga. Jakarta: Erlangga.Widayatsari.2012. Ekonomi Moneter II. Pekanbaru:Cendika InsaniWiroso.2011. Produk Perbankan Syariah. Jakarta : Lppe Usaktiwww.Worldbank.Org, Diakses Tanggal 20 Novemberwww.Bps.Go.Id, Diakses Tanggal 20 November 2017. www.Bi.Go.Id, Diakses Tanggal 20 November 2017.